Analisis Faktor-Faktor Keterlambatan Pada Pelaksanaan Pekerjaan Proyek Modernisasi Gedung Serba Guna Pt Pusri Palembang - Siddiq, Andika Maulana; Firdaus, Firdaus (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
Construction project delays often result in financial losses and schedule disruptions. This study analyzes the factors causing delays in the modernization project of the Multi-Purpose Building of PT Pupuk Sriwidjaja (Pusri) Palembang using Structural Equation Modeling (SEM). The findings reveal that ineffective communication is the dominant factor, contributing 39.9% to project delays. Inefficient execution accounts for 37.5%, while insufficient workforce skills significantly contribute 33.2%. Additionally, the interaction among these three variables exacerbates the impact of delays. This study highlights the importance of improving coordination among project stakeholders, enhancing project execution efficiency, and developing workforce capacity. These measures are crucial to preventing similar delays in future projects.